Native valve endocarditis and femoral embolism due to Granulicatella adiacens: a rare case report - K.E. Vandana, MD; C. Mukhopadhyay, MD,PDCC; N.R. Rau, MD; V. Ajith, MBBS; P. Rajath (Brazilian Journal of Infectious Diseases, 2010)
The fastidious Gram-positive cocci Granulicatella adiacens, previously known as nutritionally variant streptococci (NVS) are unusual but significant cause of endocarditis due to increased mortality and morbidity. Difficulties in reaching correct bacteriological identification, increased resistance to beta-lactam antibiotics and macrolides and complicated clinical course have contributed to problems in management of cases of infective endocarditis caused by this bacterium. We present the first Indian case of endocarditis with arterial embolus by G. adiacens in an elderly male with no pre-existing cardiac abnormality. Keywords: endocarditis, Granulicatella adiacens, femoral embolism